An experimental study of Japanese procurement auctions with endogenous minimum prices - Kenju Akai; Tatsuyoshi Saijo; Shigehiro Serizawa (Osaka University, Institute of Social and Economic Research (ISER), 2009)
Several Japanese local governments started to add endogenous minimum prices to firstprice auctions in their public procurements. Any bid less than the endogenous minimum price is referred to as abnormally low and is excluded from the procurement procedure. The endogenous minimum price is generally calculated as 80% to 90% of the average of some of the lowest bids or all bids. Therefore, producers who join this new institution have incentives to raise their bids and pull the endogenous minimum price to exclude others. We experimentally evaluate the performance of this new institution relative to the standard first-price auction which do not have any minimum price. We find that winning prices of this new institution (i) coincide with the ones of the standard first-price auction and are close to the production cost under our identical cost condition, and (ii) are higher than the ones of the standard first-price auction and diverge from the lowest production cost under our different cost condition when subjects' identifications and all their bids are revealed.
Keywords: C92; D44; L15; 330; Public procurement; First-price auction; Experiment; Abnormally low tender; Endogenous minimum price